Zero-dimensional turbulence modeling of a spark ignition engine in a Miller cycle « Dethrottling » approach using a variable valve timing system. (25th November 2021) - Perceau, Marcellin; Guibert, Philippe; Guilain, Stéphane
Highlights: A complete 0D model with in-cylinder aerodynamic prediction and turbulent combustion is proposed. Analytical calculation of quantities reduces the cost and time of the predictions. The effect of a VVT system on the performance of an EIVC Miller cycle engine is investigated. Reduction in pumping losses results in benefits of up to 1% over a wide range of engine loads. Abstract: The Miller cycle, using an early inlet valve closing, can significantly improve the overall efficiency of a spark ignition engine during partial load operations. The shorter valve intake event minimizes the need for throttling the air and so reduces the pumping losses. This method is known as "dethrottling". Indeed, the use of a variable valve lift system makes it possible to combine two different cam profiles in an engine, one for the full load operations and one for the partial loads. The benefits of this strategy, combined with a variable valve timing (VVT) system, will be explored using a new 0D model. This model can take into account the strong changes of in-cylinder turbulence generated by the VVT and their effects on the combustion. Efforts have been made to reduce the model's reliance on external inputs. Therefore, analytical calculations of quantities, such as the flame radius, have been favored. The Miller cycle can lead to indicated efficiencies around 44% and the addition of a VVT system can improve the overall efficiency up to 1% over a wide range of engine loads.